Full panorama images of 58 field plot centres during the expedition to Chukotka, summer 2016 - Stefan Kruse; Marie Rolf; Luca Farkas (PANGAEA, 2025)
During an expedition to eastern Siberia in summer 2016, full panoramic images of the sampled vegetation plots were captured for documentation purposes. Images were taken from the plot centre at breast height (1.3 m) with a tripod and a panorama head using a DSLR camera with a ultrawide angle lense. Two nadir and zenith images were taken free hand and images in 3 rounds with approximately 50% overlap. Images were stitched in Autopano Giga masking humans and artificial objects and exported to one 360x180° panorama image (10000x5000 pixel). The final panorama was blended and gaps or human shadow errors healed with GIMP resynthesizer plugin (https://github.com/bootchk/resynthesizer) and exported into one image with 7776x3888 pixels.